DOES CLIMB PEAK OF TAX AVOIDANCE FROM CSR AND COMPANY CHARACTERISTICS? STUDY IN INDONESIA - Muhammad Taufik; Elian Nevi Novita (Jurnal Magister Akuntansi Trisakti, 2022)
Departing from the realization of declining tax revenues as an indication of the tax aggressiveness existence, this paper addresses the relationship of social values, namely corporate social responsibility (CSR) and company characteristics, namely profitability, firm size, leverage, and capital intensity to three tax avoidance practice schemes, book tax difference (BTD), cash effective tax rate (CAETR), and current effective tax rate (CUETR). We accommodate legitimacy theory to seek CSR rationalization, corporate obligations that are maximize shareholder wealth, and tax regulations determine tax avoidance. The research sample is a company that is listed on the Indonesian stock exchange and publishes sustainability reporting for the 2016-2020 period where the panel data regression technique is used. The descriptive results show that BTD and CAETR do not show tax avoidance practices, on the contrary, CUETR does. The results explain that CSR is carried out based on ethical values-not profit driven, and it is proven that it does not significantly cause tax avoidance. Firm size and capital intensity are not proven to have strong ties to all tax avoidance schemes. Through CUETR, ROA and leverage are used as tools to practice tax avoidance, while BTD and CUETR are not used. This research contributes to tracing CSR driven, shows tax regulations that are used for tax avoidance, and has practical implications to show that ROA and leverage have a tendency to tax aggressiveness tools. Future research should directly examine companies involved in tax avoidance.